2007
DOI: 10.1002/micr.20301
|View full text |Cite
|
Sign up to set email alerts
|

Composite reconstruction in advanced cancer of the mouth floor: Autogenous frozen‐thawed mandibular bone and free flaps

Abstract: Mandibular symphyseal resection requires composite reconstructions, often with unsatisfactory morphofunctional results. Seven patients with advanced squamous cell carcinoma of the floor of the mouth underwent block resection with immediate reconstruction, using the removed mandible treated with liquid nitrogen and covered with a free forearm flap. In all cases, the resection was radical and no major postoperative complications occurred. Two patients died in 6 months for distant metastases and regional recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…For young patients with limited comorbidities this is the best chance for an efficient dental rehabilitation, an acceptable face profile and therefore, for a return to an almost normal social life after treatment. Unfortunately, there are some situations in which the use of a noble reconstruction may be contraindicated: (a) patients with serious comorbidities, (b) BFF failure (acute post-operative or as consequence of adjuvant treatment) and (c) relapsing disease involving the BFF [1,6,7]. The first is a condition that affects the choice of primary treatment, while the latter two affect the choice of sequential salvage treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For young patients with limited comorbidities this is the best chance for an efficient dental rehabilitation, an acceptable face profile and therefore, for a return to an almost normal social life after treatment. Unfortunately, there are some situations in which the use of a noble reconstruction may be contraindicated: (a) patients with serious comorbidities, (b) BFF failure (acute post-operative or as consequence of adjuvant treatment) and (c) relapsing disease involving the BFF [1,6,7]. The first is a condition that affects the choice of primary treatment, while the latter two affect the choice of sequential salvage treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Kelley et al firstly proposed the use of FPF in a case midface reconstruction, to optimize the vascularization of an autologous bone graft [5]. Afterwards, several authors proposed a more refined technique with FPF with autologous frozen bone for segmental mandibulectomy [6][7][8]. The first case series belong to Roselli and colleagues and Calabrese and colleagues [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This probably explains the almost complete absence of any study dealing with tongue function after mandibular symphyseal resection. The one study we found deals with seven cases in which a microsurgical radial forearm flap was used along with re-implantation of the resected bone that was treated with liquid oxygen [7]. The authors claimed good functional results without being specific about tongue function.…”
Section: Discussionmentioning
confidence: 99%